2013
DOI: 10.3389/fgene.2013.00176
|View full text |Cite
|
Sign up to set email alerts
|

Imputation of microsatellite alleles from dense SNP genotypes for parentage verification across multiple Bos taurus and Bos indicus breeds

Abstract: To assist cattle producers transition from microsatellite (MS) to single nucleotide polymorphism (SNP) genotyping for parental verification we previously devised an effective and inexpensive method to impute MS alleles from SNP haplotypes. While the reported method was verified with only a limited data set (N = 479) from Brown Swiss, Guernsey, Holstein, and Jersey cattle, some of the MS-SNP haplotype associations were concordant across these phylogenetically diverse breeds. This implied that some haplotypes pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 18 publications
0
23
0
2
Order By: Relevance
“…Although earlier studies based on a limited number of then known STRs suggested they are effectively tagged by SNPs (McClure et al. 2012, 2013), to fully explore the potential tagging relationship between STRs and SNPs, we investigated linkage disequilibrium (LD) pattern using SNPs around identified STRs, which is a simple method to understand their potential relationship without phasing STRs. We performed LD block estimation for each autosome using the 44 Holstein Bovine HD SNP array data retrieved from the Bovine HapMap panel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although earlier studies based on a limited number of then known STRs suggested they are effectively tagged by SNPs (McClure et al. 2012, 2013), to fully explore the potential tagging relationship between STRs and SNPs, we investigated linkage disequilibrium (LD) pattern using SNPs around identified STRs, which is a simple method to understand their potential relationship without phasing STRs. We performed LD block estimation for each autosome using the 44 Holstein Bovine HD SNP array data retrieved from the Bovine HapMap panel.…”
Section: Resultsmentioning
confidence: 99%
“…Although previous studies have reported that most STRs can be tagged by SNPs (McClure et al. 2012, 2013), these conclusions were mainly based on a rather limited number of known microsatellites. Because it has been impossible to produce genome-wide profiles of STR variations, the majority of STRs in the cattle genome remain undetected and unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellite genotyping is a PCR-based method that has been extensively used in parentage qualification (Tian et al 2008;Carolino et al 2009;Radko and Slota 2009); it requires a dedicated platform and skilled interpretation for accuracy (McClure et al 2013;Berry et al 2014). The polymorphic nature of microsatellite markers facilitates parentage qualification for moderately sized populations; however, larger populations require proportionally larger marker sets.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the exploration of the relationship between STRs with nearby SNPs can further help explain the results from SNP-based genome wide association studies (Brahmachary et al 2014). Although previous studies have reported that most STRs can be tagged by SNPs (McClure et al 2012(McClure et al , 2013, these conclusions were mainly based on a rather limited number of known microsatellites. Because it has been impossible to produce genome-wide profiles of STR variations, the majority of STRs in the cattle genome remain undetected and unexplored.…”
Section: Introductionmentioning
confidence: 99%